Optimization of solution polymerization of methyl methacrylate - Law, Woon Phui (2013)
In this study, optimization of reactor and jacket dynamics were carried out for the solution polymerization of MMA with toluene in batch reactor. The purpose of this study is to optimize the process condition in polymerization in order to obtain maximum conversion in minimum batch time. The gel effect, glass effect, non-linear kinetic and high exothermic reactions were considered. Initiator efficiency and overall heat transfer coefficient assumed remain constant. Optimization of MMA solution polymerization was based on three stage polymerization model (TSPM) by using MATLAB software. Ode23t solver was used in solving this moderate stiff problem. The results showed that high conversion was obtained at optimum concentration of initiator (AIBN), reactor temperature and jacket temperature. Simulation of the solution polymerization of MMA in this study showed that MATLAB was an effective and economical problem solving tools in engineering works.